Effects of planting densities and regenerations on the growth and yield of Brachiaria humidicola grown in Thua Thien Hue province - Van Loi Bui (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên)
Brachiaria humidicola is a new grass grown for cattle feed. In this study, experiments were conducted in Thua Thien Hue province, including four treatments with four planting densities of 10 x 10 cm, 20 x 20 cm, 30 x 30 cm, and 40 x 40 cm through three regenerations. The first regeneration was 60 days old, and the next two regenerations were 40 days each from the previous harvests. The experiment aimed to evaluate the effect of planting densities and regenerations on the growth and yield of B. humidicola. The results showed that the tree height, grass bed height, and number of branches/tussock varied significantly between planting densities (p < 0.05), with the highest values observed at the planting density of 30 x 30 cm (96.33 cm, 73.38 cm and 40.17 branches/tussock, respectively). The fresh matter yield, dry matter yield, and protein yield of B. humidicola also showed significant differences (p < 0.05), achieving the highest values at the planting density of 30 x 30 cm (13.87, 3.69 and 0.97 tons/ha/generation, respectively). In general, the best growth and yield of B. humidicola were maximized through regenerations at the planting densities of 30 x 30 cm.